Doing It Right: A Rule Of Law Critique Of Privatization Methodology In Nigeria - Amadi, Sam (Journal of Sustainable Development Law and Policy, 2025)
This article undertakes a rule of law critique of privatization as economic reform policy in Nigeria. The rule of law approach interrogates not just the policy rationales of the programme but also its methodology. The article distinguishes between a formal and substantive justice conception of rule of law and argues that the substantive justice conception of rule of law and its policy imperatives, sourced from the Fundamental Objectives and Directive Principles of State Policy in Chapter 2 of the 1999 Constitution, provides a veritable framework to realize the strategic goals of privatization in Nigeria.